Pengujian Black Box pada Aplikasi Sistem Absensi Karyawan Berbasis Website Menggunakan Metode Equivalent Partitions (Studi Kasus: PT Esensi Indonesia) - Aries Saifudin; Agil Muhammad; Andrian Fakhrizal; Eka Rahmat Mauluddin; Nahrowi Nahrowi; Sri Mulyati (Teknik Informatika Universitas Pamulang, 2022)
PT. ESENSI INDONESIA is a Limited Liability Company registered and headquartered in Bandung. A LOCAL Facility Services company managed by professional Indonesian children who have extensive experience in the field of Facility Services at home and abroad and already has NPMA accreditation. Attendance is the most important thing for a company because it can encourage the amount of honorarium or salary of an employee and from attendance can also see the performance of employees who are present or not. Therefore, it is very necessary to be careful in implementation so as not to hinder the company's performance. The research technique used in this employee attendance system is the Equivalent Partitions Technique which includes the results of system research, system analysis, system design, system development, system implementation. In this system, the data processing process becomes more effective and efficient and finding data is guaranteed to be simpler. The purpose of this research is to help the company's performance, especially human resources to be disciplined and reduce attendance data fraud.